Neutrophil Apoptosis in Neutropenic Patients With Hepatitis C Infection: Role of Caspases 3, 10, and GM-CSF - Aref, Salah (Springer-Verlag, 2011)
Patients with chronic HCV infection are prone to increased susceptibility bacterial infection due to neutropenia complicating the course of this disease. Neutropenia in those patients may stem from enhanced neutrophil apoptosis. However, the molecular mechanism of neutrophil apoptosis has not been clearly defined. Neutrophils harvested from 26 neutropenic patients with hepatitis C infection and nine age and sex-matched healthy control subjects were examined for the degree of apoptosis. Neutrophil apoptosis was quantified by flow cytometry through determination of annexin-V expression at 0 time (fresh neutrophil), and 24 h culture. Neutrophils from healthy subjects were also incubated with either 10% heterologous normal or neutropenic sera, with and without 10 µg GM-CSF. Caspases 3, 10 were assessed colormetrically in neutrophils at 0 times and after 24 h culture. At 0 time culture the neutrophil apoptosis of the HCV patients was in significantly higher as compared to that of normal control (P = 0.059). At 24 h culture patients neutrophils cultured with neutropenic patients own sera showed neutrophil apoptosis significantly increased as compared to that at 0 time culture and this effect was significantly attenuated in similar culture with addition of GM-CSF (P < 0.001). On the other hand patient’s neutrophil cultured with normal sera showed insignificantly increased neutrophil apoptosis at 24 h culture as compared to that at 0 time culture. Caspases 3 and 10 activities were significantly higher in patients neutrophil after 24 h cultured with patients own sera as compared to 0 time culture (P < 0.001 for both). Addition of GM-CSF to the neutrophil culture down regulates the caspases 3 and 10 activities. The correlation study between annexin-V expression and caspases activities revealed a borderline positive correlation between annexin-V and caspase 3 (r = 0.376, P = 0.058), and significant positive correlation with caspase 10 activity (r = 0.494, P = 0.01). In conclusion, these findings suggest that enhanced neutrophil apoptosis demonstrated in neutropenic patients with HCV infection might be induced through activation of caspase 10 and is attenuated by GM-CSF.